2009
DOI: 10.1007/s12052-009-0176-6
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and University-level Anthropology Textbooks: The “Missing Link”?

Abstract: Although studies analyzing the content of evolution curriculum usually focus on courses within the context of a biological sciences department or program, research must also address students and courses outside of the biological sciences. For example, using data solely from biological courses will not fully represent the scope of coverage of evolution in university education, as other fields, like anthropology, also utilize evolutionary principles. We analyzed the content of 31 university-level anthropology te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
(41 reference statements)
0
6
0
1
Order By: Relevance
“…Genetics is widely required as a core at the undergraduate level, but the topics of population and quantitative genetics are at the back of the major texts and the genetics courses are usually taught by molecular geneticists. Neither is evolution well covered in anthropology texts (White et al 2009.) White and colleagues’ (2009) study showed that these texts did not give a single accurate definition when the topic was present.…”
Section: Conclusion: Biological Determinism and Modern Genomicsmentioning
confidence: 99%
“…Genetics is widely required as a core at the undergraduate level, but the topics of population and quantitative genetics are at the back of the major texts and the genetics courses are usually taught by molecular geneticists. Neither is evolution well covered in anthropology texts (White et al 2009.) White and colleagues’ (2009) study showed that these texts did not give a single accurate definition when the topic was present.…”
Section: Conclusion: Biological Determinism and Modern Genomicsmentioning
confidence: 99%
“…However, our species is young, has very little genetic variation, has maintained relatively high levels of gene flow throughout its history, and thus has never reached the levels of differentiation between its subpopulations consistent with the identification of geographical races (see discussions of this in Templeton, 2002; also see Graves, 2011; Lawson Handley et al, 2007; Serre & Pääbo, 2004). Unfortunately, most researchers involved in projects that are affected by genetic variation do not have training or understand the historical context of evolutionary thinking concerning speciation and the role that geographical races play in the process (Nesse et al, 2010; White et al, 2009). This is illustrated by the fact that they often assume that socially defined races are legitimate biological races (Bliss, 2012; Friedman & Lee, 2013; Graves, 2010, 2011).…”
Section: Population Subdivisionmentioning
confidence: 99%
“…Given that biological anthropology is the study of humans as biological organisms (American Association of Physical Anthropologists 1996; Gundling 2010), teaching the application of evolutionary theory is also key to anthropological study. Most analyses of the efficacy of teaching evolution in the classroom focus on biology courses, where evolutionary theory is applied quite broadly to explain global biodiversity with only minimal discussion of our own taxon (Linhart 1997;Lloyd-Strovas and Bernal 2012;White et al 2009). However, university-level courses in biological anthropology directly address evolution in the human lineage (e.g., White et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Most analyses of the efficacy of teaching evolution in the classroom focus on biology courses, where evolutionary theory is applied quite broadly to explain global biodiversity with only minimal discussion of our own taxon (Linhart 1997;Lloyd-Strovas and Bernal 2012;White et al 2009). However, university-level courses in biological anthropology directly address evolution in the human lineage (e.g., White et al 2009). Although effectively teaching and communicating evolutionary theory is famously difficult for a variety of pedagogical and sociocultural reasons, including student religious beliefs and anti-intellectualism (Jensen and Finley 1996;Lloyd-Strovas and Bernal 2012;Smith 2009;Wilson 2005), teaching about evolution within the context of biological anthropology adds the complexity of requiring students to not only understand the science, but to apply it to themselves and the history of their own lineage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation